Learning Outcomes Mapping of the Three Year-Electronic Engineering Diploma in Level-5 Professional Expertise of the National Qualification Framework - Peni Handayani; Trisno Yuwono Putro; Edi Rakhman; Su Jo -Ching (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
The issue of enhancing national competitiveness, in ASEAN, has been strengthened since the establishment of ASEAN Economic Community in 2015. The recognition of graduate competence becomes very crucial for this era. Polytechnic as vocational higher education needs to prepare its graduates in order to compete in the job market, such as through professional certification. This study aimed at mapping the learning outcomes among graduates of the three year - diploma in Electronic Engineering in Polytechnic of Instrumentation and Electronic Control System on professional qualification based on level-5 Indonesian National Qualifications Framework Curriculum and Indonesia Industrial Standard Classification 2015. This study used a qualitative method. Data were collected through observation and interviews of the competent persons to provide related research data. The results showed that the learning outcomes of the three year diploma in Electronic Engineering were suitable for the work of the services and processing industry category. This map can be used to develop learning outcomes into a professional competence for a particular job in accordance with the qualifications of the graduate program.